2021
DOI: 10.3389/fonc.2021.661040
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Model and Practical Nomogram for Predicting the Outcomes of Colorectal Cancer: Based on Tumor Biomarkers and Log Odds of Positive Lymph Node Scheme

Abstract: BackgroundEmerging evidence shows that serum tumor biomarkers (TBs) and log odds of positive lymph node scheme (LODDS) are closely associated with the prognosis of colorectal cancer (CRC) patients. The aim of our study is to validate the predictive value of TBs and LODDS clinically and to develop a robust prognostic model to predict the overall survival (OS) of patients with CRC.MethodsCRC patients who underwent radical resection and with no preoperative chemotherapy were enrolled in the study. The eligible po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Patients with the same number of metastatic lymph nodes may have significantly different prognoses, thus affecting the accuracy of judging the prognosis of colorectal cancer patients. Therefore, LODDS may be a better prognostic indicator for colorectal cancer patients (36)(37)(38). Zhang et al (39) confirmed that LODDS could be divided into three proportions.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with the same number of metastatic lymph nodes may have significantly different prognoses, thus affecting the accuracy of judging the prognosis of colorectal cancer patients. Therefore, LODDS may be a better prognostic indicator for colorectal cancer patients (36)(37)(38). Zhang et al (39) confirmed that LODDS could be divided into three proportions.…”
Section: Discussionmentioning
confidence: 98%
“…Neither the LNR nor pN classification system provided additional prognostic information for patients with N0 status or harvested total lymph nodes (TLNs) < 12. Recently, an increasing number of studies have confirmed the crucial roles of LODDS in the management of several types of cancer, including CRC [ 39 44 ]. LODDS, first proposed in breast cancer in which it performed equally well as a prognostic indicator in node-positive and node-negative patients [ 16 ], was later generalized to several cancers, including CRC [ 17 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective design was applied. All samples were randomly divided (7:3 ratio) into a training set for model construction and internal validation, and a test set for model external validation [27].…”
Section: Methodsmentioning
confidence: 99%